Combined Effect of the PGR +331C > T, CYP17A1 -34A > G and CYP19A1 1531G > A Polymorphisms on the Risk of Developing Endometriosis - Cardoso, Jéssica Vilarinho; Machado, Daniel Escorsim; Ferrari, Renato; Silva, Mayara Calixto da; Berardo, Plínio Tostes; Perini, Jamila Alessandra (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose To evaluate the magnitude of the association of the polymorphisms of the genes PGR, CYP17A1 and CYP19A1 in the development of endometriosis.Methods This is a retrospective case-control study involving 161 women with endometriosis (cases) and 179 controls. The polymorphisms were genotyped by real-time polymerase chain reaction using the TaqMan system. The association of the polymorphisms with endometriosis was evaluated using the multivariate logistic regression.Results The endometriosis patients were significantly younger than the controls (36.0 ± 7.3 versus 38.0 ± 8.5 respectively, p = 0.023), and they had a lower body mass index (26.3 ± 4.8 versus 27.9 ± 5.7 respectively, p = 0.006), higher average duration of the menstrual flow (7.4 ± 4.9 versus 6.1 ± 4.4 days respectively, p = 0.03), and lower average time intervals between menstrual periods (25.2 ± 9.6 versus 27.5 ± 11.1 days respectively, p = 0.05). A higher prevalence of symptoms of dysmenorrhea, dyspareunia, chronic pelvic pain, infertility and intestinal or urinary changes was observed in the case group when compared with the control group. The interval between the onset of symptoms and the definitive diagnosis of endometriosis was 5.2 ± 6.9 years. When comparing both groups, significant differences were not observed in the allelic and genotypic frequencies of the polymorphisms PGR +331C > T, CYP17A1 -34A > G and CYP19A1 1531G > A, even when considering the symptoms, classification and stage of the endometriosis. The combined genotype PGR +331TT/CYP17A1 -34AA/CYP19A11531AA is positively associated with endometriosis (odds ratio [OR] = 1.72; 95% confidence interval [95%CI] = 1.09–2.72).Conclusions The combined analysis of the polymorphisms PGR-CYP17A1-CYP19A1 suggests a gene-gene interaction in the susceptibility to endometriosis. These results may contribute to the identification of biomarkers for the diagnosis and/or prognosis of the disease and of possible molecular targets for individualized treatments.
Keywords: polymorphisms; estrogens; endometriosis; biomarkers